RISK FACTORS IN YOUNG PATIENTS OF ACUTE MYOCARDIAL INFARCTION - Faisal, Abdul Wajid Khan; Ayub, Mohammad; Waseem, Tariq; Khan, Rao Shahzad Abdul Tawwab; Hasnain, Syed Sibitul (Journal of Ayub Medical College Abbottabad, 2011)
Background: Ischemic heart disease is a leading cause of death throughout the world. CAD has been recognized among younger age group more frequently in recent years. Very limited data is available regarding the prevalence of various risk factors in our younger patients that is why this study was planed. Objectives of the study were to look for the risk factors most prevalent in our young patient of 1st Acute Myocardial Infarction. And to also look for the number of Risk Factors present in each patient. Methods: We studied 100 consecutive patients from 16-45 years of age presenting with first acute MI. Twelve risk factors were studied namely, gender, family history of premature CAD, smoking hypertension, diabetes, dyslipidemia, obesity, mental stress (type A personality), alcohol, oral contraceptive pills (OCPs), physical activity, and diet. We divided the patients into two groups. Group A with patients 35 years of age or less and group B with patients 36-45 years of age. All risk factors were compared in both the groups. Results: Smoking, diabetes mellitus, dyslipidemia and hypertension were statistically different between the two groups. Frequency wise risk factors were lined up as male sex (91%) Diet (66%), Dyslipidemia (62%), smoking (46%), Type A personality(46%), family history (32%), diabetes mellitus (28%), sedentary lifestyle (26%), hypertension (22%), obesity (17%), alcohol (3%), and OCPs (0%) Most of the patients that is 94% had 3 or more risk factors. Conclusion: Smoking, hypertension, diabetes and dyslipidemia are the major modifiable risk factors in our young adults. If a young male who is smoker or a young female who is diabetic, presents in emergency room with chest pain, always suspect coronary artery disease. Other conventional risk factors are also prevalent but alcohol and OCPs are not a major health problem for us. Keywords: Risk factors, young patients, acute myocardial infarction